DESIGNING “VERBHOUSE” TEACHING MATERIALS TO SUPPORT TEACHING ENGLISH VOCABULARY IN JUNIOR HIGH SCHOOL - Ramadhan, Ikram Wahyu; Ikhsanudin, Ikhsanudin; Rahmani, Eka Fajar (Journal of English Education Program, 2021)
This study aimed at designing a multimedia-based product as supplementary material. It is known as VERBHOUSE. The product purposes were to help an English teacher in SMP Negeri 1 Anjongan teach English Vocabulary, especially English action verbs for year-8 students, and find out if it is suitable in supporting the English teachers. The product materials were designed based on “Bahasa Inggris for year-8 students in Junior High School” textbook. Moreover, the researcher gathered the data through an interview and that was supported with open-ended questionnaires. In analyzing the data, the researcher used an internal analysis. The researcher had developed the product within three phases of ADDIE: Analysis, Design, and Development. The researcher conducted the interview and distributed the questionnaire in the Analysis phase. The researcher then started to design the first draft in the second phase. VERBHOUSE consisted of four main menus, House, Exercises, Guide, and Credit. The product contained 40 English action verbs materials, exciting pictures, sounds, video, and provided explicit texts to the user. Furthermore, in the development phase, the researcher used an internal evaluation to measure the product. From the findings, it is indicated that the VERBHOUSE is suitable for classroom use. In short, this study has relatively succeeded in creating multimedia materials for year-8 students as supplementary materials.